STUDI META ANALISIS PERAWATAN LUKA KAKI DIABETES DENGAN MODERN DRESSING - Luh Titi Handayani* (The Indonesian Journal of Health Science, 2016)
Wound dressing technicque are growing so fast and it could help the physicians and the patients to cure the crhonic wound. The old principles said the wound care should be done in dry condition actually make the wound healing become longer because it impede the cells and collagen proliferation but too wet condition will caused maseration arround the wound. Understanding moist wound healing concept, wow to choose dressing angprinciples of wound intervention are key concepts to support wound healing proccess. Types of wound dressing that available are hydrogel, film dressing, hydrocolloid, calcium alginate, foam/absorbant dressing, anti microbial dressing, and anto microbial hydrophobic. The successfull of wound healing proccess are depend on efforts to maintain balance moist condition since its facilitate cell’s growing and collagen’s proliferation. Dressing’s choice is a decision that should be taken in order to improve wound healing proccess. And another key to succeeded is also depend on nurse capability to choose the right dressing so it can be effective and efficient so that wound care of diabetic foot could be efficient and cost effective.Key words : diabetic foot, wound healing, modern dressing